The distribution and colonization of soybean by Rhizoctonia solani AG11 in fields rotated with rice. (March 2016) - Spurlock, Terry N.; Rothrock, Craig S.; Monfort, W. Scott; Griffin, Terry W.
Abstract: From 2009 to 2012, a spatial study was conducted on soybean fields undergoing rice and soybean rotations to determine the distribution and importance of Rhizoctonia spp. Fields were sampled for soil populations by toothpick-baiting and plants were collected at growth stage V3 from GPS sampling points placed on either side of the rice levee system from the previous rice cropping year. Anastomosis group 11 (AG11) of Rhizoctonia solani, a group not recognized as causing any plant diseases on rice or soybean, was the most prevalent Rhizoctonia spp. recovered from soil and soybeans in fields assayed from 2009 to 2012. The mean recovery from the soil was 7.1 (0–94.4) and 12.2 (0–79.7) propagules/kg from fields with 48 and >96 GPS points, respectively, while the mean number of plants colonized by the fungus was 114.3 (24%) for fields with 48 GPS points and 153.8 (16%) for fields with >96 points. In 2012, all three fields assayed indicated aggregation of the soil inoculum potential of the fungus and two of the three fields indicated aggregation from the plants colonized by R. solani AG11. In all years, semi-variogram models indicated 15 measured major ranges exceeded 50 m and 11 exceeded 100 m with most of the nugget values (error) less than 5 m indicating that there is a contiguous population across space with little microstructure below the measured major range at these distances. For the three fields examined in 2012, recovery of AG11 from plants was negatively correlated with soil volumetric water content suggesting dryer areas of the field favored infection of plants. Plant stands from soil obtained for GPS locations grown under a controlled environment found a positive correlation for two of the three locations between plant stand and colonization by AG11. These studies suggest that R. solani AG11 is the dominate Rhizoctonia group in rice soybean rotations in Arkansas in the United States. R. solani AG11 opportunistically colonizes soybean and is associated with greater plant stands across fields suggesting a positive rather than a negative pathogenic role for this fungus and the host plant. Highlights: Rhizoctonia solani AG11 was the dominant R. solani population in soybean fields. The populations of R. solani AG11 were largely contiguous across the sampled area. Higher soil populations of R. solani AG11 tended to be in the wettest areas. Plants colonized most frequently by R. solani AG11 tended to be in the dryer areas. A biological association of improved plant stand and R. solani AG11 was observed.